Investing in REITs: A value-based approach - Brits, De Villiers (Department of Construction Economics and Management, 2020)
The primary purpose of this study is to test whether a value-based investment strategy will outperform a growth-based investment strategy when applied to SAREIT investment. The secondary purpose is to assess whether the SAREIT investor can discriminate between strong and weak value-REITs through sound accounting-based fundamental analysis using the F-Score Model. Building on existing research on value-based investment strategies and market efficiency, this study offers an SAREIT perspective to the existing body of knowledge on value investing theory through portfolio selection based on P/NAV, P/E, P/CF and DY ratio analysis. The holding period returns of the respective value-based portfolios are compared to their growth-based counterparts for an examination of relative performance. The evidence from this research does not offer probabilistic support that a value-based approach to SAREIT selection and investment will outperform a growth-based approach, nor that it is possible to discriminate between financially strong and weak value-REITs through sound accounting-based fundamental analysis using the F-Score Model. Further research is required to develop the said strategies and models for application to the SAREIT sector.